Research on Arc Voltage Distance-Regulating System for TIG Welding Robot. (September 2019) - Sun, Xuan; Wang, Zhiyong; Li, Yingjun; Ai, Changsheng
Abstract: In order to meet the demand of TIG welding robot for high precision and high real time, this paper presents the arc voltage distance-regulating system using expert controller. By precisely controlling the distance between the tungsten electrode and the welding seam, the arc voltage is precisely controlled, and the closed-loop control of arc voltage is realized. The simulation and experiment of MATLAB show that the arc voltage distance-regulating system's arc voltage control accuracy is 18±0.8V(6±0.32mm), which meets the precision requirements of welding robot's arc voltage control and significantly improves the welding quality.